Creating multicultural change on campus - Pope, Raechele L. 1958-; Reynolds, Amy L.; Mueller, John A. (Jossey-Bass, 2014)
"Embrace the best practices for initiating multicultural change in individuals, groups, and institutions Higher education institutions have begun to take steps toward addressing multicultural issues on campuses, but more often than not, those in charge of the task have received little to no training in the issues that are paramount in serving culturally diverse students. Creating Multicultural Change on Campus is a response to this problem, offering new conceptualizations and presenting practical strategies and best practices for higher education professionals who want to foster the awareness, knowledge, and skills necessary for multicultural change on an institutional level. In Creating Multicultural Change on Campus, the authors of the classic text Multicultural Competence in Student Affairs delve deep into key concepts in multicultural organizational development, guiding readers who want to enact change not just at the individual level, but also at the group and institutional levels.Readers will be introduced to frameworks that are crucial for creating inclusive, welcoming, and affirming campus environments. You'll also find comprehensive examples from several institutions along with specific examples of effective multicultural practices that are useful for real-world situations. The book: Provides the strategies, frameworks, and expert guidance for recognizing and addressing multicultural issues in institutions of higher learning Offers a rich understanding of both Multicultural Organizational Development (MCOD) and the Multicultural Change Intervention Matrix (MCIM) and how these models are important for evaluating environments and outcomes Is appropriate for those who serve students directly, as well as higher education leaders and administrators who create professional development programs Is designed as a practical guide and filled with specific examples to help readers apply strategies to their own campuses A much-needed resource, this book can help lead institutions toward meaningful action that will have a positive impact for all individuals in a student body and the professionals who serve them"--Provided by publisher